Ottoman cultural heritage in South Africa: Islamic legacy of the Ottoman Empire at the tip of Africa: archival records, photos and documents= Güney Afrika'da Osmanlı kültürel mirası: Osmanlı İmparatorluğu'nun Afrika'nın ucundaki İslam mirası: arşiv kayıtları, resimler ve belgeler - Gençoğlu, Halim. (Ankara)
x, 246 s.